2004
DOI: 10.1210/jc.2003-031676
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin Levels Are Associated with Coronary Atherosclerosis in Type 2 Diabetes

Abstract: Leptin signaling may promote atherothrombosis and lead to cardiovascular disease. However, whether leptin is associated with human atherosclerosis, distinct from thrombosis, is unknown. We determined the association of plasma leptin levels with coronary artery calcification (CAC), a measure of coronary atherosclerosis, in a cross-sectional study of type 2 diabetes. Leptin levels were associated with CAC after adjusting for established risk factors [odds ratio (95% confidence interval) for 5 ng/ml leptin increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
131
5
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(150 citation statements)
references
References 55 publications
8
131
5
6
Order By: Relevance
“…Increased levels of TNF-a, IL-6, CRP, leptin, and resistin have been linked to obesity and atherosclerotic cardiovascular disease (13)(14)(15)(16)(17)(18). In the present study, we found chemerin to strongly correlate with all of these markers of inflammation.…”
Section: Discussionsupporting
confidence: 64%
“…Increased levels of TNF-a, IL-6, CRP, leptin, and resistin have been linked to obesity and atherosclerotic cardiovascular disease (13)(14)(15)(16)(17)(18). In the present study, we found chemerin to strongly correlate with all of these markers of inflammation.…”
Section: Discussionsupporting
confidence: 64%
“…Leptin was also reported to stimulate calcification of endothelial cells in vitro, which may indicate an increased risk of atherosclerosis. [23,36] Although previous studies reported the association between plasma leptin levels and ED in diabetic patients, [34] such an association was not noted in the present study, in which the diabetics were excluded.…”
Section: Discussioncontrasting
confidence: 74%
“…Leptin, another hormone secreted by adipocytes, displays a strong association with CV risk factors, including insulin resistance, metabolic syndrome, and higher serum levels of inflammatory markers such as hs-CRP, plasminogen activator inhibitor-1, and soluble TNF-alpha receptors, [34,35] and thus may promote atherosclerosis. Leptin was also reported to stimulate calcification of endothelial cells in vitro, which may indicate an increased risk of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proposed as an independent risk factor for CVD and as an important link between obesity and cardiovascular risk [31,32]. Paradoxically, markedly increased plasma leptin levels were found in obese individuals, suggesting a resistance to its effects on target organs when produced excessively [33].…”
Section: The Role Of Leptin In Metabolic Syndrome and Diabetesmentioning
confidence: 99%